2018
DOI: 10.1186/s12931-018-0966-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Mycobacterium tuberculosis complex lineages as a determinant of disease phenotypes from an immigrant rich moderate tuberculosis burden country

Abstract: BackgroundGrowing evidences suggested that the Mycobacterium tuberculosis complex (MTBC) lineages can determine the clinical outcome of pulmonary and extra-pulmonary tuberculosis. However, limited data only available revealing such association of bacterial genotypes and clinical phenotypes from immigrant rich countries.MethodsA multicenter study has been carried out on a collection of 2092 (1003 extrapulmonary and 1089 pulmonary) MTBC isolates. Genotyping of all the isolates were carried out by spoligotyping a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…Regression analysis of demographical factors against site of EPTB infections showed male-gender as an independent risk factor to lymph node TB (Table 2). While similar findings have been recently established in Saudi Arabia on a national scale [25, 26], several previous reports documented increased risk of females to lymph node TB in different geographical regions [2731]. Variations in immune-related factors (e.g.…”
Section: Discussionsupporting
confidence: 80%
“…Regression analysis of demographical factors against site of EPTB infections showed male-gender as an independent risk factor to lymph node TB (Table 2). While similar findings have been recently established in Saudi Arabia on a national scale [25, 26], several previous reports documented increased risk of females to lymph node TB in different geographical regions [2731]. Variations in immune-related factors (e.g.…”
Section: Discussionsupporting
confidence: 80%
“…The TbD1-intact L1 strains are prevalent in South India and South East Asia 5 , while L7 strains are restricted to the region around the Horn of Africa [16][17][18] . The L1 strains can be subdivided in numerous sublineages 19,20 and can cause pulmonary TB as well as extrapulmonary TB in susceptible populations 21,22 . Several reports have suggested that Mtb strains from different lineages may induce unalike host responses [23][24][25][26] .…”
mentioning
confidence: 99%
“…The predominant genotype among our TBM cases in South India was that of EAI lineage (n = 16, 72.7%) followed by Beijing (n = 3, 13.6%), S-family (n = 2, 9.1%) and Delhi/CAS (n = 1, 4.5%). A study from Varghese et al reported that EAI displayed significant association to CNS TB (p-0.04) [30]. The EAI lineage strains are the most ancient Mtb strain found mostly in the southern part of India, particularly prevalent in tropical countries.…”
Section: Discussionmentioning
confidence: 98%
“…A study from Varghese et al . reported that EAI displayed significant association to CNS TB (p-0.04) [ 30 ]. The EAI lineage strains are the most ancient Mtb strain found mostly in the southern part of India, particularly prevalent in tropical countries.…”
Section: Discussionmentioning
confidence: 99%